Empowering Subcontractors in Swedish Construction with Blockchain Technology for Automated Payment Processes - Persson, Sebastian (My University, 2024)
This study addresses the pervasive issue of late payments in the Swedish construction industry, positing blockchain technology and Smart contracts as potential solutions. It aims to explore the impact of a blockchain-based Smart contract system on project management, with a focus on improving payment processes for subcontractors. By automating and making payments transparent at predefined project milestones, this research investigates the feasibility and impact of integrating blockchain technology into current project management frameworks. The research questions delve into the integration of blockchain-based Smart contracts to automate payment disbursement, the potential effects on payment delays, stakeholder collaboration, and overall project efficiency, and whether blockchain technology is necessary or if simpler solutions exist. Employing a mixed-methods approach, the study combines a literature review with interviews to construct a SWOT analysis and an Impact/Feasibility matrix. These tools are instrumental in addressing the research questions, particularly how the technology can be implemented and what the impacts are. The findings reveal that integrating blockchain-based Smart contracts can significantly streamline payment processes, offering transparency and traceability—key benefits highlighted in the literature. Interviews underscore the economic value of Smart contracts, emphasizing their potential to expedite revenue streams and save money. A recommended strategy involves legal collaboration, recruiting skilled developers, and comprehensive workforce training, ensuring a smooth transition to this new technological paradigm. The study concludes that blockchain-automated invoicing management could markedly enhance financial operations within the industry, promising timely payments and reducing invoicing delays. Such improvements are anticipated to bolster stakeholder collaboration and project efficiency. Despite the nascent stage of blockchain technology, its potential to mitigate financial disputes and delays is evident, presenting a compelling case for its implementation in the construction sector. This thesis contributes a guide for initiating an automated Smart contract payment system, underscoring blockchain technology's transformative potential for the construction industry's financial dealings.
Keywords: Blockchain Technology; Automated Payments; Constuction Industry; Smart contracts; Sustainability; Ecological Traceability; Finacial System Innovation; Web 3.0; Digital Transformation; Decentralization; Economic Effeciency; Security Enchancements; Data Integrity; Stakeholder Engagement; Technological Adoption